2018
DOI: 10.28982/josam.415215
|View full text |Cite
|
Sign up to set email alerts
|

Using multiplex PCR as a diagnostic tool to detect methicillin resistant Staphylococcus aureus

Abstract: How to cite / Atıf için: Akgün S, Sayiner HS. Using multiplex PCR as a diagnostic tool to detect methicillin resistant Staphylococcus aureus. J Surg Med. 2018;2(3):215-217. AbstractAim: The goal of this report was to deliver the methicillin resistant Staphylococcus aureus (MRSA) reports to the clinician and prevent the treatment delays, investigating the efficacy in addition to diagnostic testing and contact isolation strategies for intensive care unit (ICU) patients with MRSA. Methods: In this report, 320 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…EARS-Net 2016 [22] reported that the average rate of MRSA in S. aureus isolates is 13.7% in the European Union countries. Akgün and Sayıner [23] investigated 320 coagulase-positive S. aureus which were cultured from patients hospitalized in the intensive care unit and reported that the rate of MRSA in S. aureus isolates was 20.9% in Turkey. Khattab et al [10] isolated 8.1% MRSA among the total isolates.…”
Section: Discussionmentioning
confidence: 99%
“…EARS-Net 2016 [22] reported that the average rate of MRSA in S. aureus isolates is 13.7% in the European Union countries. Akgün and Sayıner [23] investigated 320 coagulase-positive S. aureus which were cultured from patients hospitalized in the intensive care unit and reported that the rate of MRSA in S. aureus isolates was 20.9% in Turkey. Khattab et al [10] isolated 8.1% MRSA among the total isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Wound infections are a significant problem for many types of surgery, especially vascular surgery, in the short and medium term. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common pathogens and is resistant to many antibiotics [7,8]. Methicillin-resistant Staphylococcus strains which are resistant to glycopeptides have been reported [9].…”
Section: Introductionmentioning
confidence: 99%